Development of a practical prediction score for acute renal injury after surgery for Stanford type A aortic dissection. (11th February 2020) - Dong, Ning; Piao, Hulin; Du, Yu; Li, Bo; Xu, Jian; Wei, Shibo; Liu, Kexiang
Abstract: OBJECTIVES: Acute kidney injury (AKI) is a common complication of cardiovascular surgery that is associated with increased mortality, especially after surgeries involving the aorta. Early detection and prevention of AKI in patients with aortic dissection may help improve outcomes. The objective of this study was to develop a practical prediction score for AKI after surgery for Stanford type A acute aortic dissection (TAAAD). METHODS: This was a retrospective cohort study that included 2 independent hospitals. A larger cohort of 326 patients from The Second Hospital of Jilin University was used to identify the risk factors for AKI and to develop a risk score. The derived risk score was externally validated in a separate cohort of 102 patients from the other hospital. RESULTS: The scoring system included the following variables: (i) age >45 years; (ii) body mass index >25 kg/m 2 ; (iii) white blood cell count >13.5 × 10 9 /l; and (iv) lowest perioperative haemoglobin <100 g/l, cardiopulmonary bypass duration >150 min and renal malperfusion. On receiver operating characteristic curve analysis, the score predicted AKI with fair accuracy in both the derivation [area under the curve 0.778, 95% confidence interval (CI) 0.726–0.83] and the validation (area under the curve 0.747, 95% CI 0.657–0.838) cohorts. CONCLUSIONS: We developed a convenient scoring system to identify patients at high risk of developing AKI after surgery for TAAAD. This scoring system may help identify patients who require more intensive postoperative management and facilitate appropriate interventions to prevent AKI and improve patient outcomes.